PREPARAÇÃO, CARACTERIZAÇÃO E ATIVIDADE ANTIOXIDANTE DE LIPOSSOMAS CONTENDO ÁCIDO ASCÓRBICO - Favarin, Fernanda Reis (2017)
Ascorbic acid (AA) is a water soluble vitamin and also is widely used as an antioxidant in the food, chemical and pharmaceutical industry. Among vitamins, this chemical compost is known as one of the most unstable, due to its stability can be affected by temperature, oxidation, light, enzymes, pH and metal catalysts. With the use of nanotechnology, the AA can be encapsulated in liposomes, which play the role of a shield, protecting the AA from all those factors mentioned above. The liposomes are biocompatible and biodegradable vesicular structures formed by bilayers of phospholipids around an aqueous core, but more unstable than other nanoparticles. The purpose of the liposomes usage is to protect the AA from degradation. Thus, this work aims to prepare liposomes containing ascorbic acid, to characterize and to analyze its antioxidant activity. First, an analytical method for the quantification of ascorbic acid by high performance liquid chromatography (HPLC) was co-validated. After co-validation, liposomal formulations containing 1 mg/mL ascorbic acid (LIP-A) and blank liposomal formulations (LIP-B) - without the active ingredient - were prepared for comparison using the reverse phase evaporation method. After preparation of these formulations, they were characterized according to their refractive index, average particle diameter, polydispersity index (PDI), zeta potential, pH, content, encapsulation efficiency, stability and, DPPH• and ABTS• free radical scavenging activity. In stability, three formulations were prepared and each formulation was divided into three vials, each vial was stored in a different condition. Here are the conditions: climatic chamber (40 0 °C), room temperature (25 2 °C) and refrigerator (4 1 °C). Through the results of the co-validation it was possible to realize that the ascorbic acid‘s quantification method is linear, specific and precise and, can be used for the quantification of ascorbic acid in LIP-A. The prepared liposomes presented 161 6 nm of mean vesicle diameter, a 0,231 0,02 polydispersity index, -7.3 1,1 mV zeta potential, 3,2 0,04 pH and a 19 1,1% encapsulation efficiency. The initial AA content of LIP-A was 1 mg/mL , and the initial antioxidant activity of LIP-A was 12.0 1,1 mMol and 11.4 1,4 mmol of TE/ml for the DPPH• and ABTS• radicals, respectively. The content and free radical scavenging activity varied according to the condition in which LIP-A were stored (climatic chamber, room temperature or refrigerator), because the AA’s stability depends on temperature in which it is stored. During the stability analysis, it was possible to see that LIP-B in climatic chamber condition presented instability from 15º on, while LIP-A remained stable till day 30. These results suggest that the AA, It is suggested that AA as an antioxidant leaves the liposomes more stable. The best condition for the LIP-A storage was the refrigerator one. In this condition the liposome remained stable for 30 days regarding to its mean diameter, PDI, zeta potential and pH. This condition also presented a higher content and antioxidant activity for longer than in the other ones.